2017
DOI: 10.1007/s00256-017-2579-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of core needle biopsy tract resection with local recurrence in extremity soft tissue sarcoma

Abstract: Our data suggest any influence of a CNB tract resection on LR, within the limitations of this study, is likely to be of minor clinical importance in extremity STS. Although it would be prudent to resect the CNB tract in most cases, not resecting the CNB tract is a feasible option if identification or removal of the CNB tract proves difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…It is interesting to note that a recent large cohort study depicted an incidence of needle tract metastasis of 0.5% in patients with retroperitoneal STS after a median follow‐up of 44 months . Another recent study comparing needle tract resection in patients with extremity STS found no significant difference with regard to recurrence rates compared with patients without needle tract excision . In summary, pretreatment biopsy does not compromise oncological outcomes but the decision to perform biopsy should be discussed in a multidisciplinary setting with reference to location on cross‐sectional imaging, biopsy technique, and individual patient characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that a recent large cohort study depicted an incidence of needle tract metastasis of 0.5% in patients with retroperitoneal STS after a median follow‐up of 44 months . Another recent study comparing needle tract resection in patients with extremity STS found no significant difference with regard to recurrence rates compared with patients without needle tract excision . In summary, pretreatment biopsy does not compromise oncological outcomes but the decision to perform biopsy should be discussed in a multidisciplinary setting with reference to location on cross‐sectional imaging, biopsy technique, and individual patient characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Any influence of a CNB tract resection is likely to be of minor clinical importance [17]. A recent meta-analysis demonstrates fewer complications compared with IB [2].…”
Section: Discussionmentioning
confidence: 99%
“…NTI occurs when cancer cells aspirated by the needle are disseminated in the tissues along the needle tracts. To date, several studies have been published regarding this issue [4][5][6][7][8][9][10][11][12][13][14]. Ito et al demonstrated that the incidence of NTI was 0.14% in PTC patients who underwent FNAC.…”
Section: Introductionmentioning
confidence: 99%